Renal manifestations in tuberous sclerosis patients: two case reports - Oke Rina Ramayani; Rosmayanti Rosmayanti; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 2013)
Tuberous sclerosis (TS) is a neurocutaneous disorder, characterized bymental retardation, epilepsy, and facialangiofibromas. The incidence has beenestimated to be 1 case per 6000 live births.Although rare, this disorder is a cause of mentalretardation with severe epilepsy.1 Scientists havefound manifestations of this disorder not only inbrain and skin, but also in the eyes, heart, lungs, andkidneys, so it has been renamed tuberous sclerosiscomplex (TSC).